The Checklist and Distribution of Sand Flies (Diptera: Psychodidae) of Guilan Province and Their Medical Importance With a Taxonomic Note on the Name Sergentomyia murgabiensis sintoni - Shahyad Azari-Hamidian; Behzad Norouzi; Hannaneh Maleki (Caspian Journal of Health Research, 2023)
Background: Different forms of leishmaniasis are important infectious diseases in Iran. While Rudbar County of Guilan Province has been introduced as a cutaneous leishmaniasis focus, there are few published data about the phlebotomine sand flies (Diptera: Psychodidae, Phlebotominae) of the province and their medical importance. Objectives: The present study is going to provide a review of sand fly-borne infections in Guilan Province and a checklist of sand flies of the province. Also, a note is presented on the name Sergentomyia murgabiensis sintoni. Materials & Methods: Using the main databases such as Web of Science, PubMed, Scopus, Google Scholar, Scientific Information Database (SID), IranMedex and Magiran which were searched up to September 2022 and reviewing the literature, the available data about the sand fly-borne diseases of Iran and Guilan Province were extracted and analyzed. Results: In total, 11 species representing two genera of sand flies, Phlebotomus and Sergentomyia, are found in Guilan Province. The checklist and distribution of sand flies of the province have been provided. All species of the genus Phlebotomus in the province are proven or suspected vectors of leishmaniasis. Sand fly-borne leishmaniasis (cutaneous and visceral), sand fly fever and lizard leishmaniasis, which are among the endemic infections of the province, are discussed. Also, a taxonomic note is presented on the name Sergentomyia murgabiensis sintoni. Conclusion: The prevalence of suspected or proven vectors of sand fly-borne diseases in Guilan Province is noteworthy. The study of the ecology of sand flies and detecting the exact vectors and reservoirs of leishmaniasis and phlebotomine fever by serological or molecular- specific tests in the province are recommended. Moreover, additional samplings of sand flies from localities, where have not been studied, are necessary.